1999
DOI: 10.1007/s004419900076
|View full text |Cite
|
Sign up to set email alerts
|

Modified expression of testicular gap-junction connexin 43 during normal spermatogenic cycle and in altered spermatogenesis

Abstract: In order to better understand the implications of gap junction proteins in spermatogenesis, connexin 43 (Cx43), the most abundant connexin in the testis, was evaluated in testes of wild-type mice and of two mutants with impaired spermatogenesis (ebo/ebo, and jun-d-/-mice). Reverse transcription-polymerase chain reaction (RT-PCR) amplification revealed a constitutive expression of mRNA for Cx43 in both wild-type mice and infertile mutants. In the seminiferous tubules of wild-type mice, indirect immunofluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
62
1
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 29 publications
4
62
1
3
Order By: Relevance
“…In the seminiferous tubules of human and rodent testes, this protein is distributed mainly in the basal compartment [Batias et al 1999;Risley et al 1992;Steger et al 1999]. In our study, we found that rats had undescended testes in the Flu-exposed group on PD20, but there was no difference in the level of Cx43 protein expression between rats with undescended and descended testes.…”
Section: Pd20 Are Shown Incontrasting
confidence: 37%
“…In the seminiferous tubules of human and rodent testes, this protein is distributed mainly in the basal compartment [Batias et al 1999;Risley et al 1992;Steger et al 1999]. In our study, we found that rats had undescended testes in the Flu-exposed group on PD20, but there was no difference in the level of Cx43 protein expression between rats with undescended and descended testes.…”
Section: Pd20 Are Shown Incontrasting
confidence: 37%
“…Various evidences indicate that Cx43 may be critical for control of spermatogenesis (Risley et al, 1992, Pelletier, 1996, Batias et al, 1999, Steger et al, 1999, BravoMoreno et al, 2001, Plumb et al, 2001. Data shown in the present study support the hypothesis that Cx43 plays other roles in gonadal development besides control of spermatogenesis because, by using highly specific antibodies (Bravo Moreno et al, 2001), it was demonstrated that (1) at 11.5 dpc, Cx43 mediates heterocellular contacts between precursor germ cells, identified with GCNA1 antibodies, and precursors of somatic cells, presumably preSertoli cells; (2) after gonad sexual differentiation, there are Cx43-mediated contacts between germinal and Sertoli cells that remain throughout embryonic life; and (3) Cx43 is expressed between neighboring Sertoli cells and between adjacent interstitial Leydig cells from the earliest stage of testicular differentiation at 12.5 dpc and that, in both cell types, its expression increases during fetal life.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence indicate that, among these connexins, Cx43 may be critical for gonadal development and adequate control of fertility. Cx43 is the only connexin known to be expressed in adult Leydig cells, by using immunologic (Risley et al, 1992;Pérez-Armendariz et al, 1994;Tan et al, 1996, Mok et al, 1999, Steger et al, 1999Batias et al, 1999) and electrophysiological studies (Pérez-Armendariz et al, 1994. In the mouse, its expression during postnatal development is modulated in a biphasic manner and is correlated with changes in intratesticular testosterone content (Bravo Moreno et al, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Gap junctions between the different cell types establish additional communication pathways that are, in turn, subject to regulation by paracrine and endocrine factors (Risley, 2002). In the testis within the seminiferous tubules, there is strong expression of the protein connexin 43 that correlates with the stages of spermatogenesis (Risley et al, 1992;Batias et al, 1999;Defamie et al, 2001). This protein also co-localizes with the gap junctions of the Sertoli cell junctional complex (Risley et al, 1992;Pelletier, 1995).…”
Section: The Sertoli Cellmentioning
confidence: 99%